Pengembangan Media Pembelajaran Assemblr Edu Berbasis Augmented Reality (Ar) Abad-21 Mata Pelajaran Geografi Materi Mitigasi Dan Adaptasi Kebencanaan Di Indonesia Kelas Xi Sma Negeri 4 Gorontalo - Moh. Zulkifli S Togila; Sunarty S Eraku; Nurdin Mohamad (Universitas Negeri Gorontalo, 2026)
This research aims to develop and test the feasibility of an innovative digital learning medium based on Augmented Reality (AR) through the Assemblr Edu platform for the subject of Disaster Mitigation and Adaptation in Indonesia. The development of this product was driven by low student interaction and passive learning under conventional methods, alongside the urgent need for concrete visualizations of natural phenomena such as earthquakes and tsunamis—that cannot be brought directly into the classroom. This development research follows the ADDIE model procedures, consisting of the Analysis, Design, Development, Implementation, and Evaluation phases. The resulting product integrates three core components: a Custom Geography Class, AR markers as teaching aids, and Student Worksheets (LKPD) serving as immersive instructional scaffolding. The research findings indicate that the developed learning medium meets high-quality standards based on validation from material, media, and instructional experts. Implementation among eleventh-grade students at SMA Negeri 4 Gorontalo demonstrated a very high level of practicality, with student response percentages of 93% in small-scale trials and 83.04% in large-scale trials, both falling into the